Sistem Informasi Pendaftaran Siswa Baru Madrasah Ibtidaiyah Swasta Nurul Huda Dusun Bantan Berbasis Web - Yadi, Toni Ari (Journal of Computer Science and Information System(JCoInS), 2022)
New student registration is an activity that is new Student Registration is an Annual Cycle experienced by all Educational Institutions both Public and Private Agencies. The New Student Registration Process is one of the activities that support teaching and learning activities later, the Private Madrasah Ibtidaiyah NURUL HUDA indeed really needs an Information System that can process data for new Student Candidates in the NURUL HUDA Private Madrasah Ibtidaiyah, With the new Student Registration Information System web-based is expected that new student registration officers can simplify and streamline their work, so that the inputting process for New Student Candidates can be completed in a short time, this system is also expected to be able to Minimize Data Collection Errors performed by Registration Officers.